2012
DOI: 10.1021/jp2113329
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide-Hierarchical ZnO Hollow Sphere Composites with Enhanced Photocurrent and Photocatalytic Activity

Abstract: The reduced graphene oxide (RGO)-hierarchical ZnO hollow sphere composites are prepared through a simple ultrasonic treatment of the solution containing graphene oxide (GO), Zn(CH 3 COO) 2 , DMSO, and H 2 O. The GO is reduced to RGO effectively, and the ZnO hollow spheres consisting of nanoparticles are uniformly dispersed on the surface of RGO sheets during the ultrasonic process. The optimum synergetic effect of RGO-ZnO composites is found at a RGO mass ratio of 3.56%, and the photocurrent and photodegradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
222
0
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(238 citation statements)
references
References 49 publications
8
222
0
8
Order By: Relevance
“…The ZnO-C 3 N 4 (1) composite showed smaller semicircles compare to the bare ZnO and the C 3 N 4 , indicating the lower charge-transfer resistance on the surface of the composite [25]. With the suitable amount of ZnO, the charge transfer increased since C 3 N 4 can transfer the electron to the ZnO thus, preventing the rapid electron-hole recombination.…”
Section: Photocatalytic Activity Testmentioning
confidence: 98%
“…The ZnO-C 3 N 4 (1) composite showed smaller semicircles compare to the bare ZnO and the C 3 N 4 , indicating the lower charge-transfer resistance on the surface of the composite [25]. With the suitable amount of ZnO, the charge transfer increased since C 3 N 4 can transfer the electron to the ZnO thus, preventing the rapid electron-hole recombination.…”
Section: Photocatalytic Activity Testmentioning
confidence: 98%
“…For instance, to enhance the photocurrent and photocatalytic activity, Luo et al [113] reported rGO-hierarchical ZnO hollow sphere composites through a 15-min ultrasonic treatment in which the conjunction between rGO and ZnO could be attributed to electronic interaction between the components. Zhang et al [114] have prepared a ZnO-CNT heterostructure via a hydrothermal route.…”
Section: Fabrication Of Hierarchical Zno-based Nanocompositesmentioning
confidence: 99%
“…Interestingly, this aspect necessitated their usage as antibacterial agents, noxious to microorganisms, and hold good biocompatibility to human cells [10]. Synthesis of ZnO particles with a precipitation method in alcohol solution is the most commonly used and promising lowcost route [11][12][13]. However, ZnO particles aggregate easily in solution due to van der Waals forces and surface effects [14].…”
Section: Introductionmentioning
confidence: 99%